The COVID-19 Pandemic and Bank Performance: The Role of Diversification - Tu Le; Elisa Di Febo; Thuong Do; Huy Van Cap (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study investigates the impact of diversification on the relationship between the COVID-19 pandemic and bank performance using a sample of 121 banking systems from 2016Q1 to 2021Q2. Using the system generalised method of moments, the findings show the negative impact of COVID-19 on the global banking system. This is consistent with the literature. Furthermore, the findings emphasise that diversification (e.g., lending diversification, income diversification, and geographic lending diversification) may mitigate the adverse effect of COVID-19 on banking performance. Therefore, a diversification strategy should be further considered to overcome future shocks.